PENGARUH PERILAKU OPORTUNISTIS DAN MEKANISME PENGAWASAN TERHADAP REAL EARNINGS MANAGEMENT (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Dhimas Andrean Sukoco; Dwi Ratmono (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of opportunistic behavior and control mechanisms on real earnings management. The variables used in this study are the dependent variable (real earnings management) and independent variables (financial distress, leverage, institutional ownership, number of board of commissioners, number of board of commissioners meeting, number of board of commissioners who have accounting and/or finance expertise, number of audit committee members, number of audit committee meetings, number of audit committee members with accounting and/or finance expertise).The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. By using the purposive sampling method, the sample used in this study was 83 companies for five years (2015-2019). The analytical technique used to test the hypothesis is multiple regression analysis.The results of this study indicate that financial distress, number of board of commissioners, number of board of commissioners meetings, number of audit committee members, number of audit committee meetings have a negative and significant effect on real earnings management. Meanwhile, leverage, institutional ownership, the number of members of the board of commissioners who have accounting and/or finance expertise have a positive and significant effect on real earnings management. Meanwhile, the number of audit committee members who have accounting and/or finance expertise has a negative effect on real earnings management, but not significantly.